Hubungan Kinerja Kader Kesehatan dengan Kepuasan Ibu dalam Pelayanan Posyandu Balita Mawar II Kelurahan Bareng Kota Malang Pasca Pandemi - Ferlina, Nisa; Sugijati, Sugijati; Kostania, Gita (Malang Journal of Midwifery (MAJORY), 2023)
Posyandu is a form of Community Resource Health Effort (UKBM) which is managed from, by, for and with the community, in order to empower the community and make it easier for the community to obtain basic health services. The aim of this research is to determine the relationship between Health Cadre Performance and Mother's Satisfaction in Posyandu Services for Toddlers Mawar II, Bareng Village, Malang City Post-Pandemic. This type of research is correlation analysis with a cross sectional approach. The sample in this study was 40 mothers of toddlers in the posyandu rose II area using a total sampling technique. The instrument used to collect data from this research variable was a health cadre performance questionnaire with satisfaction of mothers of toddlers with questions with a rating scale. The data collection period was 25 July - 1 August 2023. The results of the research show that there is a fairly strong relationship between the performance of health cadres and the level of satisfaction of mothers of toddlers at Posyandu Mawar II Malang City with the correlation coefficient from the results of this research being 0.629 with a positive correlation direction, the better the performance of health cadres, the higher the level of satisfaction of mothers of toddlers. From the results of this research, it is hoped that it can improve the performance of cadres in providing services regarding the role of cadres to achieve a goal, namely improving the health of children under five.